Spiral ganglion cells and macrophages initiate neuro-inflammation and scarring following cochlear implantation - Bas, Esperanza; Goncalves, Stefania; Adams, Michelle; Dinh, Christine; Bas, Jose M.; Van De Water, Thomas R.; Eshraghi, Adrien A. (Frontiers in Cellular Neuroscience, 2015)
Conservation of a patient’s residual hearing and prevention of fibrous tissue/new bone formation around an electrode array are some of the major challenges in cochlear implant (CI) surgery. Although it is well known that fibrotic tissue formation around the electrode array can interfere with hearing performance in implanted patients, and that associated intracochlear inflammation can initiate loss of residual hearing, little is known about the molecular and cellular mechanisms that promote this response in the cochlea. In vitro studies in neonatal rats and in vivo studies in adult mice were performed to gain insight into the pro-inflammatory, proliferative, and remodeling phases of pathological wound healing that occur in the cochlea following an electrode analogue insertion. Resident Schwann cells, macrophages/microglia, and fibroblasts had a prominent role in the inflammatory process in the cochlea. Leukocytes were recruited to the cochlea following insertion of a nylon filament in adult mice, where contributed to the inflammatory response. The reparative stages in wound healing are characterized by persistent neuro-inflammation of spiral ganglion neurons and expression of regenerative macrophages in the cochlea. Accordingly, genes involved in extracellular matrix deposition and remodeling were up-regulated in implanted cochleae. Maturation of scar tissue occurs in the remodeling phase of wound healing in the cochlea. Similar to other damaged peripheral nerves, M2 macrophages and de-differentiated Schwann cells were observed in damaged cochleae and may play a role in cell survival and axonal regeneration. In conclusion, the insertion of an electrode analogue into the cochlea is associated with robust early and chronic inflammatory responses characterized by recruitment of leukocytes and expression of pro-inflammatory cytokines that promote intracochlear fibrosis and loss of auditory hair cells and spiral ganglion neurons important for hearing after CI surgery.